(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The introduction of marketing in the field of higher education can have a beneficial effect on its development in this sphere of public relations and, in particular, is the key to the successful operation of an educational institution. The use of a scientifically based method in this direction determines the relevance of marketing research in the field of higher education.